Aftertaste. Series 1 [videorecording (DVD)] - De Fina, Julie; Bate, Matthew (Acorn, 2022)
When his latest outburst goes viral, volatile celebrity chef Easton West flees back to his Australian hometown and tries to reinvent himself through an unlikely partnership with his 19-year-old pastry wunderkind niece.